A follow-up study of post-COVID-19 syndrome in hospitalized children with Omicron variant infection in Wuhan - Tang, Chunjiao; Wang, Shouyi; Fan, Jingyi (Frontiers in Pediatrics, 2024)
Background：Since the Chinese government changed its COVID-19 prevention and control policies, the rapid spread of the omicron variant resulted in a pervasive surge of infections throughout the nation, particularly affecting children. Although the acute symptoms of children infected with COVID-19 are milder compared to adults, the impact of post-COVID-19 syndromes ( PCS ) on the growth and development of children should not be ignored. The clinical manifestations, treatment methods, and long-term effects of children are significantly different from those of adults, making it necessary to understand the phenotype of children with PCS in order to effectively manage their health. Methods： The study focuses on hospitalized children infected with omicron variant in